Live and Heat-Killed Lactobacillus rhamnosus ATCC 7469 May Induce Modulatory Cytokines Profiles on Macrophages RAW 264.7 - Jorjão, Adeline Lacerda [UNESP]; De Oliveira, Felipe Eduardo [UNESP]; Leão, Mariella Vieira Pereira; Carvalho, Cláudio Antonio Talge [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP]; De Oliveira, Luciane Dias [UNESP] (Wiley, 2015)
This study aimed to evaluate the capacity of Lactobacillus rhamnosus and/or its products to induce the synthesis of cytokines (TNF-α, IL-1β, IL-4, IL-6, IL-10, and IL-12) by mouse macrophages (RAW 264.7). Three microorganism preparations were used: live L. rhamnosus (LLR) suspension, heat-killed L. rhamnosus (HKLR) suspension, and the supernatant of a heat-killed L. rhamnosus (SHKLR) suspension, which were cultured with macrophages (37°C, 5% CO2) for 2 h and 30 min. After that, cells were cultured for 16 h. The supernatants were used for the quantitation of cytokines, by ELISA. The results were compared with the synthesis induced by lipopolysaccharide (LPS) and analysed, using ANOVA and Tukey test, 5%. LLR and HKLR groups were able to significantly increase the production of TNF-α, IL-6, and IL-10 (P < 0. 05). SHKLR also significantly increased the production of TNF-α and IL-10 (P < 0. 05) but not IL-6 (P > 0. 05). All the L. rhamnosus suspensions were not able to produce detectable levels of IL-1β or significant levels of IL-4 and IL-12 (P > 0. 05). In conclusion, live and heat-killed L. rhamnosus suspensions were able to induce the synthesis of different cytokines with proinflammatory (TNF-α and IL-6) or regulatory (IL-10) functions, suggesting the role of strain L. rhamnosus ATCC 7469 in the modulation or in the stimulation of immune responses.